CAN GREEN MARKETING BE ACHIEVED? DRIVEN BY SOCIAL CAPITAL TOWARDS PRODUCT INNOVATION AND CUSTOMER ORIENTATION - Setini, Made (Jurnal Ilmiah Manajemen & Bisnis, 2022)
Business development activities that care about the environment are certainly important for a business, and environmentally friendly activities have led to awareness of the practice green marketing. The application of green marketing is not only intended for a better environment but also as a competitive advantage towards better marketing performance. This study analyzes customer orientation, product innovation moderated by social capital on the implementation of green marketing for non-culinary SMEs. Data were collected from 100 SMEs from various sectors, and collected using a 5-point Likert scale questionnaire with Google for media, analyzed using SEM-PLS, SmartPLS as tools. The results show that social capital is a moderator in the relationship between customer orientation, product innovation and green marketing. The direct relationship between marketing orientation and innovation has a significant positive impact on Green Marketing. Social capital becomes a bridge for exchanging information between customers, the product to be purchased, and how the product will be marketed. The existence of information from one individual to an individual or group makes positive energy that is very important in growing concern for the environment.